Indirect gonioscopy system for imaging iridocorneal angle of eye - Perinchery, Sandeep Menon (2019)
Current clinical optical imaging systems do not provide sufficient structural information of trabecular meshwork (TM) in the iridocorneal angle (ICA) of the eye due to their low resolution. Increase in the intraocular pressure (IOP) can occur due to the abnormalities in TM, which could subsequently lead to glaucoma. Here, we present an indirect gonioscopy based imaging probe with significantly improved visualization of structures in the ICA including TM region, compared to the currently available tools. Imaging quality of the developed system was tested in porcine samples. Improved direct high quality visualization of the TM region through this system can be used for Laser trabeculoplasty, which is a primary treatment of glaucoma. This system is expected to be used complementary to angle photography and gonioscopy.